Near infrared absorption cross sections for ethane broadened by hydrogen and nitrogen. (February 2020) - Hewett, Dan; Bernath, Peter; Zhao, Jianbao; Billinghurst, Brant
Highlights: High resolution absorption cross sections of ethane (C2 H6 ) in the near infrared (1900–6000 cm -1 ). Cross sections for N2 and H2 broadened ethane. Measurements performed between 205 and 295 K. Useful for spectra of Giant Planets and Titan. Abstract: Near infrared absorption spectra of ethane (C2 H6 ) were recorded in the 1800–6200 cm −1 region by high resolution Fourier transform spectroscopy (Bruker IFS 125 HR) at the Canadian Light Source (CLS). Absorption cross sections were obtained for pure samples and with nitrogen or hydrogen as broadening gases as appropriate for astronomical environments. Corrections to the cross sections were made using data from the Pacific Northwest National Laboratory (PNNL) infrared database.